Bilinguals' creativity and an argument for paradigm shift. Issue 1 (9th July 2019) - Pandharipande, Rajeshwari V.
Abstract: This paper examines the centrality of the notion of bi/multilinguals' creativity in Kachru's work and its significant role in the paradigm shift in research on world Englishes. Here, it is suggested that bilingual creativity became the catalyst for treating non‐native varieties of English not as 'deviant, ' but rather as different from so‐called native Englishes. The world Englishes (WE) paradigm has moved from treating 'native' English as the exclusive center/norm of the language to accepting many centers of English (the pluricentricity of English), which has had a number of implications for both bilingual creativity and the study of the intelligibility of non‐native varieties of English.